2007
DOI: 10.1088/0953-2048/20/12/005
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of c-axis-correlated 1D pinning centers and vortex Bose glass in Ba–Nb–O-doped ErBa2Cu3Oy films

Abstract: We report the effectiveness of barium niobate as a needle-type vortex pinning center, as well as a change in the vortex state in Ba–Nb–O (BNO)-doped ErBa2Cu3Oy thin films. BNO doping was effective for improving critical current properties for a magnetic field direction parallel to the c axis of a matrix film and induced the generation of columnar defects with diameters of 5–25 nm. The irreversibility lines were also changed by the BNO doping and were similar to those of heavy-ion-irradiated YBa2Cu3Oy crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…The BENO nanorods could provide effective -axis correlated pining centers at a lower growth temperature [6], [8]. The seems to relate closely with nanorod growth.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The BENO nanorods could provide effective -axis correlated pining centers at a lower growth temperature [6], [8]. The seems to relate closely with nanorod growth.…”
Section: Introductionmentioning
confidence: 85%
“…The seems to relate closely with nanorod growth. Another recent report, it was demonstrated that BENO nanorods were thinner in diameter and distributed at higher density at a lower [6], [9]. However, the nanorods became curved with a deviation from the -axis direction of the film at a lower .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…BaZrO 3 has been used most commonly as a target impurity addition [4], and has been shown [18] to be able to self-organize into correlated nano-rods within the film microstructure. More recently, BaNb 2 O 6 and BaSnO 3 [19,20] and BaSnO 3 has been added to YBCO [21]. Another secondary phase addition to the target that proved to create strong pinning centres is Gd 2 Ba 4 Cu-WO 12 [22].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, BaNb 2 O 6 (BNO)-doped Er123 bulk material was [13]. We reported the transport properties of a BNO-doped Er123 film [14].…”
Section: Introductionmentioning
confidence: 99%